Isolation of major phenolics from Launaea spinosa and their protective effect on HepG2 cells damaged with t-BHP. (3rd March 2016) - Abdallah, Hossam; Farag, Mohamed; Osman, Samir; Kim, Da hye; Kang, Kyungsu; Pan, Cheol-Ho; Abdel-Sattar, Essam
Abstract: Context : Some Launaea species (Asteraceae) are used traditionally to treat liver oxidative stress. Objective : The present study investigates the protective effects of isolated compounds from Launaea spinosa Sch. Bip. (Asteraceae) against oxidative stress on t -BHP-induced HepG2 cells. Materials and methods : Major phenolic content from flowering aerial parts of L. spinosa was isolated and identified. The protective effects of isolated compounds (10 and 20 μM) against oxidative stress induced by tert -butyl hydroperoxide ( t -BHP) in HepG2 cells were investigated through the measurement of aspartate aminotransferase (AST), alanine transaminase (ALT), and superoxide dismutase (SOD) levels. Results : A new phenolic compound identified as 2, 3-diferulyl R, R -(+) methyl tartrate (6 ), in addition to five known metabolites, esculetin (1 ), esculetin-7- O -d -glucoside (cichoriin) (2 ), fertaric acid (3 ), acacetin-7- O -d -glucoside (4 ), and acacetin-7- O -d -glucuronic acid (5 ), were isolated. Oxidant-induced damage by 200 μM t -BHP in HepG2 cells was inhibited by compounds1, 4, and5 (10 and 20 μM), or quercetin (10 μM; positive control). The protective effects of compounds1, 4, and5 were associated with decreasing in AST, ALT, and SOD levels. Compound4 (20 μM) decreased the AST level from 128.5 ± 13.9 to 7.9 ±1.8 U/mL. Meanwhile, compound1 (20 μM) decreased ALT activity from 20.3 ± 7.0 to 7.6 ± 2.4 U/mL, while compound5 decreased SOD levels from 41.6 ± 9.0 to 28.3 ± 3.4 mU/mg. Conclusion: The major phenolic compounds isolated from L. spinosa displayed a significant cytoprotective effect against oxidative stress, leading to maintenance of the normal redox status of the cell.